Um olhar crítico sobre a concessão urbanística em São Paulo: formulação pelo executivo, audiências públicas e regulamentação pelo legislativo - Souza, Felipe Francisco de (2010)
The urban issue in Brazil was sanctioned by the Federal Constitution in 1988 and by the Federal Law of the Statute of the City, in 2001. After that, the development of municipal laws, related to comprehensive participatory plans and specific urban planning tools, has been brought out with the promise of confronting the social inequalities that are part of the urban scenario in Brazil. Given this context, this dissertation aims to analyze the process of making and regulation of an urban planning tool called concessão urbanística (urban grant, in English) at three different moments. First: considering its origin in the Executive estate, during the mayor Marta Suplicy’ management (PT – “Labor Party”, 2001-2004) and its inclusion in the Strategic Comprehensive Plan for São Paulo (2002-2012). Second: considering the mayor José Serra (PSDB – “Social Democracy Party”, 2005-2006) and the mayor Gilberto Kassab’s (DEM – “Democrats Party”, 2006-2008/2009-current) management strategy of promoting 'revitalization” policies in the São Paulo downtown, through the Nova Luz project (New Light, in English), employing the concessão urbanística planning tool. Third, since the moment when the Civil Society’ discussions about concessão urbanística Bill (Bill 87, 2009) were first reported to the City Council until its approval by the Legislature (Law 14.917, 2009). By investigating this process, this study intends to contribute with an analysis on the concessão urbanística inclusion in the public government’s agenda, considering the strategies chosen by the Civil Society actors in order to influence the actions upon the Municipal Government. The goal is to achieve a better understanding of the restricted production of urban public policies in the democratic contexts of the postConstitution of 1988 and the post-City Statute of 2001.